THE K (KAKANGARI) CHONDRITE GROUPLET - Weisberg M.K.; Prinz M.; Clayton R.N.; Mayeda T.K.; Grady M.M.; Franchi I.; Pillinger C.T.; Kallemeyn G.W. (My University, 1996)
The Kakangari, LEW 87232, and Lea Co. 002 chondrites have a similar set of petrologic and oxygen isotopic characteristics that distinguishes them from other chondrite groups. They are here established to constitute a single chondrite grouplet--the K (after Kakangari) chondrites. The K chondrites have (1) high matrix abundances (33-77 vol%) as do carbonaceous chondrites, (2) metal abundances (6-10 vol%) that are similar to the H group ordinary chondrites, (3) average mafic silicate compositions (average Kakangari olivine = Fa2.2; enstatite Fs4.4) that indicate an oxidation state intermediate between H and E chondrites, (4) matrix that differs from that in other chondrite groups in being enstatite-rich with compositions more Mg-rich (average = Fs3) than those in the chondrules, (5) refractory lithophile element abundances (<1 CI) similar to those of the ordinary chondrites, (6) wholerock oxygen isotopic compositions that plot below terrestrial fractionation line (Δ 17O = -1.2 to -1.8), near the CR chondrites, and (7) chondrule oxygen isotopic compositions that form a mixing line ranging from compositions similar to those of the E chondrite chondrules (Δ 17O near zero) to more negative Δ 17O values. The K chondrites studied here are unequilibrated petrologic type 3 and are therefore K3 chondrites. K chondrites are not affiliated with any of the three--E, O, or C--chondrite classes but have some characteristics that are similar to those of each class. Their characteristics also do not fit the concept that the petrologic and chemical properties of chondrite groups are a smooth function of formation at specific heliocentric distances from the sun.